Impact of Sn Particle-Induced Mask Diffraction on EUV Lithography Performance Across Different Pattern Types - Seungchan Moon; Dong Gi Lee; Jinhyuk Choi; Junho Hong; Taeho Lee; Yasin Ekinci; Jinho Ahn (Photonics)
This study investigates the differences in the lithographic impact of particles on the pellicle surface depending on the type of extreme ultraviolet (EUV) mask pattern. Using an EUV ptychography microscope, we analyzed how mask imaging performance is affected by locally obstructed mask diffraction caused by a 10 μm × 10 μm patterned tin particle intentionally fabricated on the pellicle surface. The resulting critical dimension variations were found to be approximately three times greater in line-and-space patterns than in contact hole patterns. Based on these findings, we recommend defining the critical size of particles according to the mask pattern type to optimize lithographic quality.